Lucretius plays Epicurus: Kant and pleasure, the sublime, nature (Itinera, 2014)
The dissertation aims at uncovering the following topics: ethics, nature and sublime. In particular, it focuses on the above topics in relation to the theories of Epicurus and Immanuel Kant. The analysis takes into account the following scripts: “De Rerum Natura”, “Critica del Giudizio”, “Metafisica dei Costumi”, “Osservazioni sul sentimento del bello e del sublime”. They are evaluated to drouw the similarities and the differences between the two philophical perspectives.